Detachment 101: a microcosm of the evolutionary nature of warfare. - Withers, Kristine (Kansas State University, 2011)
Detachment 101's experiences provide a microcosm view of the evolutionary nature of warfare, and also demonstrates the understanding of Fourth Generational Warfare concepts by the Detachment.
Keywords: History; Military History; History (0578); Military History (0722); Military Studies (0750)